E-Science: The Grid and the Semantic Web. - Roure, D; Hendler, J (2004)
The application of e-science to grid computing and advanced Semantic Web technology was described. The service-oriented approach known as the Open Grid Services Architecture (OGSA) was developed as Web Services enhancement to meet grid application requirements. The Semantic Web offered tools which supported instant messaging and visualization to enhance group peripheral awareness, planning and task support. The e-science vision proved as interface between humans and the Grid while, the Semantic Web combined the interlinked layers of information flow.